MEMILIH MEDIA PEMBELAJARAN YANG TEPAT DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA SAAT PELAJARAN PENDIDIKAN AGAMA KRISTEN - Dewi Clara Simanjuntak; Bella Priskilla br. Sitepu; Damayanti Nababan (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
Students' active learning in learning is an important and fundamental issue that must be understood, realized and developed by every teacher in the learning process. Learning activeness is a motor in learning activities. It is not enough for students to just listen and take notes, but students also have to participate directly by providing responses during learning. The learning process is essentially to develop students' active learning through various interactions and learning experiences, where students' active learning can be achieved through group learning activities or individual learning. Learning media acts as a tool to make it easier for students to receive messages from the teacher. According to Hamalik in Arsyad, the use of learning media in the teaching and learning process can generate new desires and interests, generate motivation and stimulation of learning activities, and even have psychological influences on students. The use of learning media at the learning orientation stage will greatly help the effectiveness of the learning process and delivery of messages and lesson content at that time.